Hubungan Lingkungan Sosial, Pengetahuan Ibu, Dan Status Gizi Terhadap Produksi ASI Pada Ibu Nifas Di Rumah Sakit Firdaus Jakarta Utara : The Relationship between Social Environment, Mother's Knowledge, and Nutritional Status on Breast Milk Production in Postpartum Mothers at Firdaus Hospital, North Jakarta - Tiga, Maria Herlina (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Mother's Milk (ASI) is an emulsion of fat in a solution of protein, lactose, and inorganic salts secreted by the mother's mammary glands and is useful as baby food. Breast milk production is the process of forming breast milk which involves the hormone prolactin and the hormone oxytocin. The purpose of this study was to determine the relationship between social environment, mother's knowledge, and nutritional status on breast milk production in post-partum mothers at Firdaus Hospital, North Jakarta in 2023. Methods: The design of this study was an analytic descriptive quantitative method with a cross-sectional approach with a total sample of 52 mothers. Post-partum who conducted an examination at Firdaus Hospital, North Jakarta. Results: The results of the chi-square statistical test showed that there was a relationship between social environment (p-value 0,011); mother's knowledge (p-value 0,011) and nutritional status (p-value 0,000) with milk production in post-partum mothers. Discussion: The conclusion in this study is that there is a significant relationship between the social environment, mother's knowledge and nutritional status on the production of breast milk in post-partum mothers at Firdaus Hospital, North Jakarta in 2023. Suggestions for post-partum mothers to be able to improve their nutritional fulfillment during the breastfeeding period by implementing good and correct eating patterns in accordance with the nutritional adequacy rates recommended by health workers.